Design, Formulation, and Evaluation of Aloe vera Gel-Based Capsaicin Transemulgel for Osteoarthritis - Narayana Charyulu Rompicherla; Punam Joshi; Amitha Shetty; Kalvatala Sudhakar; Hawraz Ibrahim M. Amin; Yachana Mishra; Vijay Mishra; Aqel Albutti; Naif Alhumeed (MDPI AG, 2022)
Topical treatments are a potential therapeutic option for the therapy of osteoarthritis, with significant data supporting the effectiveness and safety of topical formulation. Topical gel formulations may offer an alternative to oral formulations to relieve osteoarthritis (OA) pain while decreasing systemic exposure. Topical capsaicin transemulgel may represent an effective and safe alternative. The transemulgel was prepared from aqueous Aloe vera gel and Carbopol 934 with capsaicin in clove oil emulsion. The optimized transemulgel of capsaicin showed a pH of 6.1 ± 0.1 and viscosity of 15263-998 cps. Data from in vitro diffusion demonstrated improved permeability properties. The formulation caused no skin irritation when applied topically. The optimal transemulgel spreadability was found to be 20.23 g·cm/s. In vitro and ex vivo studies of the optimized formulation were performed. The skin irritant test was performed on rat skin with an optimized and marketed formulation. Both showed no irritation on the skin. The transemulgel of the capsaicin with Aloe vera gel was proven to be effective for osteoarthritis therapy.